Analytical modelling and sensitivity analysis of Gallium Nitride-Gate Material and, dielectric engineered- Schottky nano-wire fet(GaN-GME-DE-SNW-fet) based label-free biosensor. (November 2022) - Sharma, Swati; Nath, Vandana; Deswal, S.S.; Gupta, R.S.
Abstract: An analytical model of nanogap embedded Gallium Nitride Gate- Material and Dielectric Engineered- Schottky Nano-Wire Field Effect Transistor (GaN-GME-DE-SNW-FET) for implementation as a label-free biosensor is introduced . An expression for the surface potential is attained by resolving the 1-D Poisson equation and 2-D Laplace equation utilizing a superposition method. A Model for the threshold voltage is also developed to analyz e the sensitivity of the biosensor. The projected model also contains the repercussion of barrier height dropping at the metal-semiconductor intersection along with Dielectric Engineering (DE) using high-k (HfO 2 ) material and Gate Material Engineering (GME) using metal m 1 with workfunction φ m 1 and m 2 with workfunction φ m 2 . The sensitivity of biosensor's has been studied for diverse dielectric constant and charge densities immobiliz ed within the nanogap cavity. A comparative study has also been done between Gallium nitride-based (GaN- GME-DE-SNW-FET) and Silicon-based (Si-GME-DE-SNW-FET) Label-free biosensors. The developed analytical model is verified and validated using ATLAS- TCAD device simulations.